New methods of windowing for reducing the out of band emission with low complexity in the 5G waveform - Hammoodi, Ahmed Talaat (2022)
Various 5G waveform candidates are used for wireless communication in multicarrier waveform design. This specifically includes Filtered-Orthogonal Frequency Division Multiplexing (F-OFDM) and Universal Filtered Multicarrier (UFMC) waveforms adopted in the high-speed 5G system and beyond. Previous literature studies showed that a high level for out of band emission (OOBE) and attaining accurate KPIs in real applications are the main obstacles in the 5G communication. Thus, the present study contributed in three new methods in the time domain, namely, Kaiser Hankel subband Window (KHW), hybrid window group subcarrier-windowing (HWG subcarrier windowing), and Convolution New Window type-windowing (CNW windowing) to suppress the value of OOBE in F-OFDM and UFMC and improve Power Spectral Density (PSD) without degradation of Bit Error Rate (BER) in the system. On the other hand, two methods were proposed in the frequency domain to decrease the OOBE while maintaining a low computational complexity, namely, Array window subcarrier windowing (AWsubcarrer-windowing) and the Half subcarrier edge windowing (HSE-windowing). The OOBE decrease for KHW, HWG, and CNW is 70%, 75%, and 80% for the ACLPRG for KHW, HWG, and CNW, respectively. Moreover, ACLPRG for AW and HSE is 78% and 81% of either the traditional in frequency domain approach. The merging also reduces suppression ACLPRG OOBE by 88%. Also, difficult real-addition and multiplication operations have been reduced by 33-45%. The new methods helped reduce the value of OOBE without affecting the system’s KPIs. The waveform could also coexist with a legacy system without affecting the core KPIs and key quality indicators (KQIs) by reduce the OOBE in the 5G waveform. Moreover, the study found that lowering OOBE did not increase system complexity. These findings have ramifications for academics, and 5G communication.